Description of the ambulance services participating in the Aus-ROC Australian and New Zealand out-of-hospital cardiac arrest Epistry - Beck, B.; Bray, Janet; Smith, K.; Walker, T.; Grantham, H.; Hein, C.; Thorrowgood, M.; Smith, A.; Inoue, Madoka; Smith, T.; Dicker, B.; Swain, A.; et al. (2016)
OBJECTIVE: The present study aimed to describe and examine similarities and differences in the current service provision and resuscitation protocols of the ambulance services participating in the Aus-ROC Australian and New Zealand out-of-hospital cardiac arrest (OHCA) Epistry. Understanding these similarities and differences is important in identifying ambulance service factors that might explain regional variation in survival of OHCA in the Aus-ROC Epistry. METHODS: A structured questionnaire was completed by each of the ambulance services participating in the Aus-ROC Epistry. These ambulance services were SA Ambulance Service, Ambulance Victoria, St John Ambulance Western Australia, Queensland Ambulance Service, St John Ambulance NT, St John New Zealand and Wellington Free Ambulance. The survey aimed to describe ambulance service and dispatch characteristics, resuscitation protocols and details of cardiac arrest registries. RESULTS: We observed similarities between services with respect to the treatment of OHCA and dispatch systems. Differences between services were observed in the serviced population; the proportion of paramedics with basic life support, advanced life support or intensive care training skills; the number of OHCA cases attended; guidelines related to withholding or terminating resuscitation attempts; and the variables that might be used to define 'attempted resuscitation'. All seven participating ambulance services were noted to have existing OHCA registries. CONCLUSION: There is marked variation between ambulance services currently participating in the Aus-ROC Australian and New Zealand OHCA Epistry with respect to workforce characteristics and key variable definitions. This variation between ambulance services might account for a proportion of the regional variation in survival of OHCA.